Crowd-Sourced Filmmaking: Despair is Your Friend - Rose, Mitchell (The International Journal of Screendance, 2015)
If the pilot of a 767 died, could you land the plane while the control tower talked you through it over the radio? I've always been fascinated (obsessed) by the idea of getting people to do complicated things, remotely, via instructions. And that's what I wanted to undertake when I made my new crowd-sourced film, Globe Trot. I got 54 filmmakers in 23 countries (representing all seven continents including Antarctica) to each contribute two seconds of precise footage that I edited together. 15 months of work, resulting in a 3-minute film. A second impetus for this project was experimentation I've been doing the last few years in what we could call "Hyper-Matchcutting"—films where every adjacent edit is perfectly aligned in position and continuity.